2017
DOI: 10.1590/s0004-2803.201700000-39
|View full text |Cite
|
Sign up to set email alerts
|

Flow Mediated Dilation and Carotid Intima Media Thickness in Patients With Chronic Gastritis Associated With Helicobacter Pylori Infection

Abstract: -Background -Endothelial dysfunction is one of the early stages of vascular diseases. Objective -The aim of this study was to investigate the endothelial dysfunction markers in patients with chronic gastritis associated with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 19 publications
(19 reference statements)
1
16
0
2
Order By: Relevance
“…Atherosclerosis like vascular events have been reported in patients with H. pylori infection [18,19]. Judaki et al [18] reported more prominent vascular changes in patients with H. pylori-positive chronic gastritis than in H. pylori-negative chronic gastritis. Some studies have also reported decreased gastric microcirculation in patients with H. pylori infection [12,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atherosclerosis like vascular events have been reported in patients with H. pylori infection [18,19]. Judaki et al [18] reported more prominent vascular changes in patients with H. pylori-positive chronic gastritis than in H. pylori-negative chronic gastritis. Some studies have also reported decreased gastric microcirculation in patients with H. pylori infection [12,20].…”
Section: Discussionmentioning
confidence: 99%
“…This abnormalities occurs by different mechanisms like changes in serum lipid levels, and the metabolism and production of oxidative stress [17]. Atherosclerosis like vascular events have been reported in patients with H. pylori infection [18,19]. Judaki et al [18] reported more prominent vascular changes in patients with H. pylori-positive chronic gastritis than in H. pylori-negative chronic gastritis.…”
Section: Discussionmentioning
confidence: 99%
“…Using high-frequency ultrasonographic imaging of the brachial artery, it was found that endotheliumdependent flow-mediated vasodilation (FMD) was significantly lower in the subjects with seropositive antibodies to H. pylori than in the ones with seronegative antibodies to H. pylori, while endothelium-independent nitroglycerin-induced vasodilation was similar in both groups [50]. Similarly, another study with patients with chronic gastritis associated with H. pylori infection demonstrated that the level of FMD in patients with positive H. pylori infection was significantly lower than those with negative H. pylori infection and the healthy control group [51]. Studies also showed that the levels of C-reactive protein and soluble intercellular adhesion molecule-1 (ICAM-1) were significantly higher in subjects with seropositive antibodies to H. pylori than in those with seronegative antibodies to H. pylori [50].…”
Section: H Pylori Infection and Endothelial Dysfunction 41 H Pylori Infection And Endothelial Dysfunction In Patientsmentioning
confidence: 90%
“…Some endothelial dysfunction biomarkers such as endothelin-1 (ET-1), soluble vascular cell adhesion molecule-1 (sVCAM-1), and intercellular adhesion molecule-1 (ICAM-1), were significantly increased in patients with H. pylori infection, indicating that patients with H. pylori infection are at risk of endothelial dysfunction. 65,66 In addition, some available evidence has revealed that the H. pylori virulence factor VacA may be involved in endothelial dysfunction by leading to vacuole formation in endothelial cells and has a significant proatherogenic effect. 67 Based on the above findings, some researchers believe that H. pylori infection could start and (or) accelerate the process of AS.…”
Section: Helicobacter Pylori and Endothelial Dysfunctionmentioning
confidence: 99%